2014
DOI: 10.1021/la5040323
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Unquenchable and Thermally “On–Off” Reversible Room Temperature Phosphorescence of 3-Bromoquinoline Induced by Supramolecular Gels

Abstract: Ion-unquenchable and thermally on-off reversible room temperature phosphorescence (RTP) can be induced by entrapping 3-bromoquinoline (3-BrQ) into supramolecular gels formed by the self-assembly of a sorbitol derivative (DBS). In comparison with conventional substrates inducing RTP, the gel state 3-BrQ/DBS can produce strong RTP due to the efficient restriction of the vibration of 3-BrQ. Notably, the rather inconvenient deoxygenation is no longer necessary in the preparation of 3-BrQ/DBS gels. The produced RTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
(62 reference statements)
1
27
0
Order By: Relevance
“…Another approach to induce room‐temperature phosphorescence by aggregation or hindered motion was described by Yang and co‐workers in 2015 (Figure ) . Their idea involved the trapping of 3‐bromoquinoline ( 20 ) inside supramolecular gels, which were formed by the spontaneous self‐assembly of sorbitol derivatives (DBS).…”
Section: Aggregation‐induced Phosphorescencementioning
confidence: 99%
“…Another approach to induce room‐temperature phosphorescence by aggregation or hindered motion was described by Yang and co‐workers in 2015 (Figure ) . Their idea involved the trapping of 3‐bromoquinoline ( 20 ) inside supramolecular gels, which were formed by the spontaneous self‐assembly of sorbitol derivatives (DBS).…”
Section: Aggregation‐induced Phosphorescencementioning
confidence: 99%
“…As such, intensely phosphorescent materials are largely known to exist in inert gases and at very low temperatures,w hich in turn limits their practical applications. [20] So far,s everal strategies have been applied to minimize the intermolecular and intramolecular motions to activate the phosphorescence emission, which include hostguest doping systems with supramolecular gel entrapping, [21] metal-organic framework coordination [22] and rigid solid protection, [4] polymer assistance, [23,24] and crystal formation. [6][7][8][9][10][11][12][13] These discoveries sparked several attempts to find ag eneral strategy to design more of such materials for various applications.Itwas found that to yield efficient RTP, several key factors have to be considered.…”
mentioning
confidence: 99%
“…[5] Recently,r esearchers discovered several examples of pure organic materials that exhibited persistent phosphorescence in air and at room temperature. [20] So far,s everal strategies have been applied to minimize the intermolecular and intramolecular motions to activate the phosphorescence emission, which include hostguest doping systems with supramolecular gel entrapping, [21] metal-organic framework coordination [22] and rigid solid protection, [4] polymer assistance, [23,24] and crystal formation. Thefirst is to promote intersystem crossing (ISC), and the second is to suppress the non-radiative relaxation pathways such as intermolecular motions.…”
mentioning
confidence: 99%
“…Furthermore, the deoxygenation of the systems is usually required. Recently, we reported study on the RTP of 3‐bromoquinoline resided in supramolecular gels . The RTP of 3‐bromoquinolin was found to be ion‐unquenchable and thermally on–off reversible due to the unique ordered structure of supramolecular gels.…”
Section: Introductionmentioning
confidence: 99%